Direct relationship between aging and overcrowding in the ED, and a calculation formula for demand projection: a cross-sectional study. Issue 1 (8th January 2013) - Kawano, Takahisa; Nishiyama, Kei; Anan, Hideaki; Tujimura, Yuka
Abstract : Objective: Although it has been suggested that the increase in older population contributes to overcrowding in emergency departments (EDs), there are limited data defining this relationship. This study examines whether patients' mean age per day affects length of ED stay. Methods: This cross-sectional analysis evaluated how patient age affects length of ED stay. The study was conducted at an ED attached to Fujisawa City Hospital, Japan, between 1 November 2009 and 31 October 2010. Patients scheduled to visit for childbirth and patients under age 15 were excluded. The primary outcome measure was the relationship between length of ED stay and patient age. The secondary outcome was the relationship between patient age and patient dispositions indicated by column chart and 100% staked column chart. Results: Over the study period, there were 17 744 patient visits to the ED. The study included 15 840 (89.3%) patients. The mean (SD) age of these patients was 56.9 (21.5) years. In single and multiple linear regression analyses, mean patient age per day was an important factor in length of ED stay for the total number of patients visiting the ED (single linear regression analysis: regression coefficient=1.59 min/year, r 2 =0.005, p<0.001; multiple linear regression analysis: regression coefficient=0.72 min/year, r 2 =0.24, p<0.001). The ratio of admitted and transferred patients increased with patient age. Conclusion: The increase in older patients visiting the ED has a direct significant negative effect on overcrowding in the ED.